Why art criticism?: a reader - Söntgen, Beate; Voss, Julia (Hatje Cantz Text, 2021)
Intro -- Inhalt -- Foreword -- Why Art Criticism? An Introduction -- Passion, Performance, and Soberness: Denis Diderot - Beate Söntgen -- Essays on Painting - Denis Diderot -- In Conversation: Clemens Brentano, Achim von Arnim - Johannes Grave -- In Front of a Friedrich Seascape with Capuchin Monk - Clemens Brentano, Achim von Arnim -- Feelings Before Friedrich's Seascape - Heinrich von Kleist -- Emotional Collectivities: Julius Meier-Graefe - Stephanie Marchal -- Fellows in Reality - Julius Meier-Graefe -- The Leak: Berta Zuckerkandl - Julia Voss -- The Klimt Affair - Berta Zuckerkandl -- Klimt's letter to the Education Ministry -- Crafts and the Spiritual: Ananda K. Coomaraswamy - Monica Juneja -- The Indian Craftsman - Ananda K. Coomaraswamy -- Practical Formalist: Roger Fry - Beate Söntgen -- The Futurists - Roger Fry -- The Case of the Late Sir Lawrence Alma Tadema, O. M. - Roger Fry -- Independent Gallery: Vanessa Bell and Othon Fries - Roger Fry -- Agitation: Sergei Tretyakov - Valerija Kuzema -- The Work of Viktor Palmov - Sergei Tretyakov -- Photo-Notes - Sergei Tretyakov -- Snapshot: Alexander Rodchenko - Margarete Vöhringer -- Against the Synthetic Portrait, For the Snapshot - Alexander Rodchenko -- Decomposition: Georges Bataille - Malte Rauch -- Critiques - Georges Bataille -- Decolonizing Art History: Ananda K. Coomaraswamy - Parul Dave Mukherji -- Why Exhibit Works of Art? - Ananda K. Coomaraswamy -- Advocating the Collective: Luis Vidales - Camilo Sarmiento Jaramillo -- The Aesthetic of Our Time - Luis Vidales -- Colombian Painting - Luis Vidales -- Materialism and Proximity: Francis Ponge - Isabelle Graw -- Note on the Hostages, Paintings by Fautrier - Francis Ponge -- Censorship and the Authorial "I": Lothar Lang - Valerie Hortolani and Valerija Kuzema -- Annotations on Painting in Leipzig, with an Update on Tübke - Lothar Lang.